Distribution of The Sensible Jacques Ranciere - Rosida Erowati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
This paper aims to discuss the problem of aesthetic in modern Indonesian literature in its relation with the politic. In contrast with the traditional understanding of the aesthetic and politic, this paper offers an alternative perspective abstracted by the French aesthetic philosopher, Jacques Rancière, to look into five problems concerning this matter. First, the mechanism of inclusion/exclusion in defining the aesthetic in relation to politic. This problem leads to the second, that is the definition of aesthetic as a distribution of sensibility which consists of the visible, the intelligible, and the possible where the main goal is to shatter the social hierarchy. In addition to this, the definition of revolutionary works relies not on the engagement of the artist into the political field, but on the succeed to bridging the hierarchical migration. Moreover, the presumption of equality as the foundation of the revolutionary in aesthetic, thus a popular work does not always consider as such. And finally, art as an act for the people to position themselves in participating in the polis, thus the idea of literacy is a very important instrument to make sure the subject to emancipate. By considering these problems, the question of when is the birth of modern Indonesian literature needs to be re-assessed.